Redox dynamics in seeds of Acer spp: unraveling adaptation strategies of different seed categories - Fuchs, Hanna; Staszak, Aleksandra M.; Vargas, Paola A.; Sahrawy, Mariam; Serrato, Antonio J.; Dyderski, Marcin K.; Klupczyńska, Ewelina A.; Głodowicz, Paweł; Rolle, Katarzyna; Ratajczak, Ewelina (Frontiers in Plant Science, 2024)
Seeds of woody plant species, such as those in the Acer genus like Norway maple (Acer platanoides L.) and sycamore (Acer pseudoplatanus L.), exhibit unique physiological traits and responses to environmental stress. Thioredoxins (Trxs) play a central role in the redox regulation of cells, interacting with other redox-active proteins such as peroxiredoxins (Prxs), and contributing to plant growth, development, and responses to biotic and abiotic stresses. However, there is limited understanding of potential variations in this system between seeds categorized as recalcitrant and orthodox, which could provide insights into adaptive strategies. Here, we investigated the expression changes of the genes Trx-h1, 1-Cys-Prx, and TrxR NTRA in the embryonic axes of maturing, mature, and stored seeds from these two Acer species. The expression of Trx-h1 and TrxR NTRA throughout seed maturation in both species was low. The expression of 1-Cys-Prx remained relatively stable throughout seed maturation. In stored seeds, the expression levels were minimal, with slightly higher levels in sycamore seeds, which may confirm that recalcitrant seeds remain metabolically active during storage. Using proteomic analysis and DDA methods, a library of 307 proteins interacting with Trx-h1 was constructed, comprising 69 from Norway maple and 233 from sycamore, with distinct profiles in each seed category. Recalcitrant seed axes displayed a wide array of metabolic, stress response, and signaling proteins, suggesting sustained metabolic activity during storage and the need to address oxidative stress. .Conversely, the orthodox seed axes presented a protein profile, reflecting efficient metabolic shutdown, which contributes to their extended viability. The results of the study provide new insights into seed viability and storage longevity mechanisms. They enhance the understanding of seed biology and lay the foundation for further evolutionary research on seeds of different categories.